Beginning POJOs - Sam-Bodden, Brian (Apress, 2012)
Java’s history is a thorny and convoluted one. From its origins at Sun, better known for its hardware than its software, Java was born as a stealth project targeting consumer devices. Along came the Web, and Java provided the only way to do anything remotely close to rich animation. Applets running on the HotJava Browser showcasing a dancing Duke was my “oh, now that’s cool” moment of 1995. So we set out to write enormously large applets that were slow to run and then the browser wars began and you could only guess whether it was going to run or your user would see a big gray box on their browsers. Today applets still have their niche, mostly in the least-expected places, like the computer in an oil lube bay or a conveyor-controlling application in a distribution center. But Java was still the new kid on the block. In the late ’90s, Web applications were being built on the CGI platform and a trove of scripting languages. At that point Java came into its own with the servlet API and what was viewed as the golden hammer of its time, the EJB specification. At that point I was already tainted by the complexity of the Distributed Component Object Model (DCOM) and Common Object Request Broker Architecture (CORBA), so to paraphrase Bruce Tate, I ate the elephant and it was good! Well, guess what? By the time we entered the 21st century the elephant already was the animal of choice in large corporate IT departments, it started to face fierce competition in the wild. It had to run on Pearls, fight Pythons and lately tried to avoid the red light at the end of the tunnel (is that a Ruby on Rails?).